2021
DOI: 10.3390/cells10102519
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological Basis of Increased Risk for Suicidal Behaviour

Abstract: According to the World Health Organization (WHO), more than 700,000 people die per year due to suicide. Suicide risk factors include a previous suicide attempt and psychiatric disorders. The highest mortality rate in suicide worldwide is due to depression. Current evidence suggests that suicide etiopathogenesis is associated with neuroinflammation that activates the kynurenine pathway and causes subsequent serotonin depletion and stimulation of glutamate neurotransmission. These changes are accompanied by decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 155 publications
(275 reference statements)
2
32
0
6
Order By: Relevance
“…Deficiency of this and other neurotransmitters (such as norepinephrine) has been observed in cases of suicide since the deficiency of these neurotransmitters in critical places in the brain results in depressive states. Such a deficiency can occur due to insufficient production, excessive neurotransmitter reuptake in the synaptic cleft or failure of the receptor system ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Deficiency of this and other neurotransmitters (such as norepinephrine) has been observed in cases of suicide since the deficiency of these neurotransmitters in critical places in the brain results in depressive states. Such a deficiency can occur due to insufficient production, excessive neurotransmitter reuptake in the synaptic cleft or failure of the receptor system ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…For biological measures, we will explore whether suicide re-attempt could be associated with alterations of the HPA axis, neuroplasticity, and inflammation, including a recent toxoplasmosis infection. These biological systems are highly connected since glucocorticoids dysregulation could lead to increased inflammatory activity and impaired neuroplasticity ( 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the kynurenine level was higher in suicide attempters compared to depressed patients. Conversely, PIC is neuroprotective and its level was reduced in the CSF and blood, and the PIC/QUIN ratio was decreased in the CSF and blood of patients with SB [ 113 ]. A detailed description of the involvement of KP in suicide is out of the scope of this review and can be found elsewhere [ 114 , 115 , 116 ].…”
Section: Biological Alterations Underlying Suicidal Behaviourmentioning
confidence: 99%